Socrative Sebagai Student Response System dalam Pembelajaran Daring Bahasa Arab - Majidatun Ahmala; Saudati Alfira Rahmatillah; Tadarrosatul Hikmiyah (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2021)
Purpose-Analyzing the socratives effectiveness as a media-based assessment of student response systems in the Arabic lessons during online classes.  Design/Methodology/Approach-This research is using descriptive-qualitative methods and was done in MAN Sidoarjo. This research methods used a simple random sampling by students of the 11 th grades IPA 1 and 2 with total population is 25 students. The data assemblings has collected by observation, interviews, and documentation. Furthermore, the data will be processed by source triangulation.   Findings: Socrative is an effective medium to provide teaching servis on Arabic lessons. There are three types of questions in the socrative methods and it was multiple choice, true/false, and short answer, and it might be able to cover the eight question type that have been developed by the Arabic language teacher of MAN Sidoarjo. This statement is giving a prove to us that socative methods colud be very helpful to facilitate teachers in developing strategies for creating exam questions, and from 25 sampling, 19 students are expressed their interest in using socrative in Arabic online learning class for various reasons.  Research Limitation/Implications: This reseach can’t reached more deeper than the reseach on space race and exit ticket because the socrative menu that being used in the field is focused on quick question, however, even though this reseach was focused on quick question, researcher found that socrative used maximally by the teacher. They use it to create various types of question in purpose to get feedback from students.